Ocular topotecan pharmacokinetics following topical administration to rabbits for diffused anterior retinoblastoma - Taich, Paula Juliana (2017)
Objectives: We characterized and compared the in-vivo absorption of topotecan into the aqueous humor after instillation of aqueous and ointment formulations. Methods: A lanolin/petrolatum ointment was used. New Zealand rabbits were instilled with topotecan solution (6 μg, group A), a single 10 μg dose of topotecan ointment (group B) or with five 10 μg doses of topotecan ointment (group C). Aqueous humor samples were collected at different times. Corneal samples were collected only for group A. Topotecan was quantified using HPLC, and pharmacokinetic parameters were calculated. Acute corneal epithelial toxicity was assessed after multiple instillations of topotecan ointment. Key findings: Total topotecan maximum aqueous humor concentration (Cmax) was 16.1, 69.9 and 287 ng/ml in group A, B and C, respectively. A single dose of topotecan ointment increased threefold and sevenfold the aqueous humor Cmax, and exposure compared to the aqueous formulation. Aqueous humor concentrations from group C eyes were substantially above the cytotoxic concentration for retinoblastoma cells. No corneal toxicity was evident after ointment instillation. Conclusions: Topotecan penetrated into the aqueous humor of the rabbit eye after multiple doses of an ointment in concentrations pharmacologically active against retinoblastoma cells without eliciting acute toxicity. Topotecan ointment may translate to the clinical treatment of anterior segment disseminated retinoblastoma.